Carbon Footprint of Additively Manufactured Precious Metals Products - Mario Schmidt; Jochen Heinrich; Ingwar Huensche (Resources)
Traditionally, precious metals are processed by either lost-wax casting or the casting of semi-finished products followed by cold or hot working, machining, and surface finishing. Long process chains usually conclude in a high material input factor and a significant amount of new scrap to be refined. The maturing of Additive Manufacturing (AM) technologies is advantageous with regard to resources among other criteria by opening up new processing techniques like laser-based powder bed fusion (LPBF) for the production of near net shape metal products. This paper gives an insight into major advantages of the powder-based manufacturing of precious metal components over conventional methods focusing on product carbon footprints (PCF). Material Flow Cost Accounting (MFCA) for selected applications show energy and mass flows and inefficient recoverable losses in detail. An extended MFCA approach also shows the greenhouse gas (GHG) savings from avoiding recoverable material losses and provides PCF for the products. The PCF of the precious metals used is based on a detailed Life Cycle Assessment (LCA) of the refining process of end-of-use precious metals. In the best case, the refining of platinum from end-of-life recycling, for example, causes 60 kg CO2e per kg of platinum. This study reveals recommended actions for improvements in efficiency and gives guidance for a more sustainable production of luxury or technical goods made from precious metals. This exemplary study on the basis of an industrial application shows that the use of AM leads to a carbon footprint of 2.23 kg CO2e per piece in comparison with 3.17 kg CO2e by conventional manufacturing, which means about a 30 percent reduction in GHG emissions and also in energy, respectively.